A strategic management plan for 07 San Jose Printing Press (2012-2017) - Gumia, Roluzendelio V.; Digal, Larry N.; Concepcion, Sylvia B. (Davao City School of Management, University of the Philippines Mindanao, 2011)
07 San Jose Printing Press like any other company in the industry has chosen to pursue the path of growth and escalation in its printing process in an aim to utilize existing and untapped opportunities for the company. At present, the company has taken pleasure on an informal business process arrangement and had it worked for them advantageously. To ensure that every participating building block that composes 07 San Jose Printing Press (07SJPP) has focused its energy in a solitary goal, working towards the same ideals for the future and to assess and adjust the organization?s direction in response to a changing environment, it is therefore a must to spend some time not only in the aspect of creating but also in the reflecting on and defining the organization?s strategic plan. METHODOLOGY. In conceptualizing the strategy of 07 San Jose Printing Press, the proponent has used mixed methodologies in an aim of creating a meaningful direction for the institution?s future. In general, qualitative methods provide a better understanding of the context in which the development of institutional strategy can occur while qualitative methodologies, on the other hand, provide an assessment of how the institution is currently functioning (National Science Foundation; 1997). Industry structure has a strong influence in determining competitive rules. According to Porter, the state of competition in an industry depends on five basic competitive forces, namely industry competitors, suppliers, buyers, potential entrants, and substitutes. SCOPE OF THE INDUSTRY. The printing and publishing industry has three major subsectors classified according to the products or services they offer. These subsectors are (1) newspapers and periodicals, (2) books and pamphlets, and (3) commercial and job printing and other allied industries. FIRMS IN THE INDUSTRY. According to the Center for Business and Economics Research and Development of the De La Salle University, the number of firms belonging to the printing and publishing industry as of the year 1995 is at 2,755, with small firms (those employing less than 10 employees) accounting for about ¾ of the total number. CUSTOMERS. According to the Printing Industries Association of the Philippines, an identified three-fold purpose of printed and published materials that served as a criterion in segmenting the markets of the industry were as follows; As a producer of reading materials, the printing and publishing industry serves the general reading public (including students, teachers, professional), and institutional buyers (e.g. libraries), in educating, providing data/information, or entertaining readers. As a producer of a medium of communication, the industry serves individuals and institutions in disseminating information and influencing perceptions/decisions (e.g., advertisements). As a producer of documents, the industry serves private and government institutions by manufacturing receipts, forms (accounting forms), document, and similar printed materials. Bargaining power of Customers. According to Porter, buyers compete with the industry by forcing down prices, bargaining for higher quality or more services, and playing competitors against each other. Buyers of the printing and publishing industry have a strong bargaining power over commercial printers because the products and services offered by the industry are largely standard and undifferentiated. Buyers can, therefore, choose a printing press that offers the lower price. Moreover, the intense rivalry among the players in the printing and publishing industry has worked for the benefit of customers (Tereso Tullao Jr. et.al.; 2001). Suppliers. The in-depth analysis of the Printing Industry of the Philippines has placed the categorical class for the major suppliers of the printing and publishing industry. On the study, it was discussed that amongst the subsectors are the suppliers of paper, ink, fuel, and printing equipment. Also important suppliers are companies that provide transportation, electricity, and postal and messenger services. Also, among the printing machines and equipment used by print shops are the following: printing and binding machines, computer-aided machines, computers, computer printers, and scanners, electronic pre-press equipment, photocopying machines, communication equipment and gadgets, finishing equipment and suppliers, graphic art tools and supplies, laminating machines, and silkscreen and signage equipment among others (Tereso Tullao Jr. et al.; 2001).
Thesis, Graduate (Master in Management)--University of the Philippines Mindanao, December 2011.